Do continuous and intermittent running exercises affect leukocyte count? Comparison of acute and chronic effects - Ozan, M.; Buzdagli, Y.; Siktar, E.; Baygutalp, N. K.; Bakan, E. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2023)
Background. It is widely accepted that physical exercise can cause changes in the immune system. Acute bouts of exercise can alter the number and function of leukocytes, but the degree of white blood cell increase depends on the intensity and duration of the exercise. Purpose. This aim is to examine the acute and chronic effects the white blood cell count and subsets in the bloodstream of the per- formance of continuous and intermittent running exercise as well as body composition. Material and Methods. In the adult category, the age, sports age and height of actively engaged in weight sports are respectively; total of 40 top-elite male athletes with CRG: 26.3±2.67 years, 9.1±1.08 years, and 177.3±5.06 cm and IRG: 25.6±2.79 years, 8.2±2.66 years and 179.9±6.51 cm participated. A one-way analysis of variance (ANOVA) with repeated measurements was used to iden- tify differences between measurement points for leukocyte and subset values. The comparison of the groups effect was made by repeated measurements with a two-way (group x time) ANOVA. Results. According to the data obtained; in the CRG group, WBC, lymphocyte, neutrophil, monocyte, eosinophil values and in the IRG group; WBC, lymphocyte, neutrophil and monocyte values were found to be significantly different within the group between weeks. (p<0.05) When the CRG and IRG groups were compared, there was no significant difference between the groups. (p>0.05) Conclusions. Our study reveals that leukocyte and subset values acutely increase after both continuous and intermittent exercises in elite athletes, but when examined from a chronic point of view, blood values after exercise program are similar to resting states. Besides that, continuous and intermittent aerobic running exercises are thought to increase the performance and endurance of athletes.